1976
DOI: 10.1007/bf01538963
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of three methotrexate-resistant phenotypes from Chinese hamster ovary cells

Abstract: Three mechanisms for resistance to methotrexate (Mtx) have been identified in Chinese hamster ovary (CHO) cells selected from resistance to this drug. First-step selections produce cells with either an apparent structural alteration in the enzyme dihydrofolate reductase (class I), or a decreased permeability to the drug (class II). Mutagenesis with ethyl methanesulfonate increases the proportion of Mtx-resistant cells 5-10-fold. Second-step selections to higher resistance using class I resistant cells as paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(150 citation statements)
references
References 27 publications
3
147
0
Order By: Relevance
“…However, the specific productivity decreased upon further increase of MTX level (Kim et al, 2001). Gene amplification by MTX selection is generally obtained by gradual increase of MTX selection pressure rather than rapid increase as single-step high-level resistance to MTX may result in mechanisms other than dhfr-mediated gene amplification, such as altered MTX transport properties (Assaraf and Schimke, 1987;Kaufman, 1990;Sirotnak et al, 1981) or an altered, MTX-resistant DHFR enzyme (Flintoff and Essani, 1980;Flintoff et al, 1976;Haber and Schimke, 1981). Hence, a gradual increase, instead of a rapid increase, of MTX concentration is more effective for constructing high-producer recombinant CHO cell lines as previously shown by Nakanishi et al (1997) and Yoshikawa et al (2000a).…”
Section: Resultsmentioning
confidence: 99%
“…However, the specific productivity decreased upon further increase of MTX level (Kim et al, 2001). Gene amplification by MTX selection is generally obtained by gradual increase of MTX selection pressure rather than rapid increase as single-step high-level resistance to MTX may result in mechanisms other than dhfr-mediated gene amplification, such as altered MTX transport properties (Assaraf and Schimke, 1987;Kaufman, 1990;Sirotnak et al, 1981) or an altered, MTX-resistant DHFR enzyme (Flintoff and Essani, 1980;Flintoff et al, 1976;Haber and Schimke, 1981). Hence, a gradual increase, instead of a rapid increase, of MTX concentration is more effective for constructing high-producer recombinant CHO cell lines as previously shown by Nakanishi et al (1997) and Yoshikawa et al (2000a).…”
Section: Resultsmentioning
confidence: 99%
“…These changes in the properties of DHFR suggested that MTX resistance was the result of mutations in the protein (Albrecht et al, 1972;Flintoff et al, 1976;Goldie et al, 1980). This was subsequently confirmed.…”
Section: Alterations In Dhfrmentioning
confidence: 91%
“…The approach used was chemical mutagenesis followed by selective pressure with dihydrofolate reductase (DHFR) inhibitors, a technique applied in this and other laboratories (9,35,40). The agents used were MTX, a classical antifolate that forms polyglutamate derivatives in cells, and 5,8-dideaza-N ␣ -(-4-amino-4-deoxypteroyl)-N ␦ -hemiphthaloyl-1-ornithine (PT632), a novel antifolate with 10-fold higher affinity for DHFR and RFC that does not form polyglutamate derivatives (34) and has very low affinity for low-pH transporters in several tumor cell lines (32).…”
mentioning
confidence: 99%